2018
DOI: 10.4103/jlp.jlp_176_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory standards institute versus European committee for antimicrobial susceptibility testing guidelines for interpretation of carbapenem antimicrobial susceptibility results for Escherichia coli in urinary tract infection (UTI)

Abstract: BACKGROUND:Carbapenems show excellent activity against resistant uropathogens, and they are the antibiotics of choice for urinary tract infections (UTIs). The choice of carbapenem prescription is strongly influenced by antimicrobial susceptibility testing (AST) report. With the publication of recent AST guidelines by the European Committee on AST (EUCAST), we were curious to evaluate the difference in results between Clinical and Laboratory Standards Institute (CLSI) and the EUCAST guidelines for the interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…Nineteen out of 20 articles reported significant discrepancies in one or more pathogen–antimicrobial combination, nearly always due to a reduction in susceptibility rates and/or increase in resistance rates when applying more restrictive EUCAST breakpoints. A notable exception was a study from India [8] that reported higher meropenem and imipenem susceptibility rates in urinary E. coli isolates using EUCAST breakpoints, underlining the lack of alignment between the two systems even for such important combinations. A trend of reduced susceptibility and/or higher resistance rates with EUCAST breakpoints was evident in the additional 53 articles where both EUCAST and CLSI breakpoints were used for susceptibility interpretation, many of which were reports of AMR surveillance data.…”
mentioning
confidence: 99%
“…Nineteen out of 20 articles reported significant discrepancies in one or more pathogen–antimicrobial combination, nearly always due to a reduction in susceptibility rates and/or increase in resistance rates when applying more restrictive EUCAST breakpoints. A notable exception was a study from India [8] that reported higher meropenem and imipenem susceptibility rates in urinary E. coli isolates using EUCAST breakpoints, underlining the lack of alignment between the two systems even for such important combinations. A trend of reduced susceptibility and/or higher resistance rates with EUCAST breakpoints was evident in the additional 53 articles where both EUCAST and CLSI breakpoints were used for susceptibility interpretation, many of which were reports of AMR surveillance data.…”
mentioning
confidence: 99%
“…Other studies have also suggested that the in vitro resistance to nalixidic acid could be used as a pointer to the actual level of in vitro resistance to ciprofloxacin (Campioni et al, 2017;Klemm et al, 2018). According to the Clinical and Laboratory Standard Institute (CLSI) guidelines, the resistance to any antimicrobial agent in the fluoroquinolone drug class has an impact on the resistance of other antimicrobial agents within this drug class (Sahu et al, 2018). This implies that the resistance observed by the Salmonella enterica to nalidixic acid in this study is a pointer to the development of resistance to other members of the fluoroquinolone class of antimicrobial agents such as ciprofloxacin and norfloxacin in humans in the Calabar region.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of inhibition zone was measured using caliper (Rosco Diagnostica, Taastrup, Denmark). We interpreted the inhibition zone diameter using CLSI 15 . This study used nystatin with a dose of 100,000 UI/ml (pharma chemistry Ltd, Bekasi, Indonesia) and fluconazole at a dose of 2 mg/ml (pharma chemistry Ltd, Bekasi, Indonesia)…”
Section: Methodsmentioning
confidence: 99%